Platforma e-learningowa narzędziem w nauczaniu zdalnym osób dorosłych - Nowak-Żółty, Edyta; Bożerocki , Tomasz (Studia Edukacyjne, 2020)
The authors of the article address issues concerning the teaching of the Polish language of adults living in the Czech Republic, Lithuania and Latvia via remote education, using the e-learning platform. They point to the unique approach of adults to education by means of IT tools (e-learning platform). The aim of the authors’ search is to try to answer the question: “Is learning Polish using an e-learning platform effective?” The authors also want to learn about the platform itself as a tool in adult learning.